1932
DOI: 10.1111/j.2044-8279.1932.tb03143.x
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Mental Tests to University Students

Abstract: Résumé. L'APPLICATION DE TESTS À DES ÉTUDIANTS D'UNIVERSITÉ. (II). Les résultats d'un questionnaire démontrent que ces étudiants qui réussissent mal des tests d'intelligence générale à “University College,” Londres, mais qui réussissent bien un examen d'université subséquent, s'intéressent plus à leur travail, et travaillent plus d'heures par jour selon des méthodes plus intelligentes. Ils ne se laissent pas distraire par des préoccupations sociales mais se dirigent vers le but étroit academique. D'autre part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1940
1940
1940
1940

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Questionnaires. In a number of studies questionnaire material or items on tests which distinguished better from poorer students also point to the conclusion that what is commonly called " introvert " behavior is associated with better grades than its opposite (61,183,304).…”
Section: Personality Interests Attitudesmentioning
confidence: 99%
See 3 more Smart Citations
“…Questionnaires. In a number of studies questionnaire material or items on tests which distinguished better from poorer students also point to the conclusion that what is commonly called " introvert " behavior is associated with better grades than its opposite (61,183,304).…”
Section: Personality Interests Attitudesmentioning
confidence: 99%
“…The total number involved here was 118. And in another (304), among 1800 students, "discrepant failures"high on intelligence but low on examinations-were compared with " discrepant distinguished " students-low on intelligence but high on examinations. The former were found to be more frequently handicapped by mental disabilities of the anxiety type.…”
Section: Personality Interests Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…Through these studies, however, there is a consistent trend for a small correlation to be found between academic grades and introversion, and in many cases correlations of significant size have been found between these two variables (82,107,164,253,270). It seems that introversion provides a condition which favors academic success, possibly by reducing the tendency for the student to be distracted by outside events.…”
Section: Nonintellectual Factors In Academic Successmentioning
confidence: 86%